PEMETAAN POLA-POLA BRAND IDENTITY MELALUI SENSORIS INDERA PENCIUMAN (OLFACTORY) DALAM MEMBANGUN SOCIAL ENGAGEMENT Studi Olfactics pada Outlet Ritel di Mal-Mal di Jakarta - Dicky Pradana (Universitas Mercu Buana, 2017)
The brand identity of the retail sphere generally used only three sensory senses: visual, hearing and tactile. It becomes interesting when our olfactory senses also able to recognize the brands in the retail sphere. This research departs from the thought, that man can fast a moment not eat, closed to not see, close the ears to not hear, moment not touch something. But while man is still alive, man will not stop breathe and attracted to something through olfactory senses. This study aims to map out the patterns of brand identity communication through olfactory sensory in retail brands in Mal such as Wakai, Johnny Andrean. XXI, Rotiboy, BreadTalk etc. The method uses case study analysis with qualitative approach. For that chosen is descriptive explorative approach which is a type of research that aims to find a new knowledge that previously did not exist. This research reveals Olfactory branding in the retail sphere contributes holistically in providing communication patterns that generate brand identity through the meaning of self-experience and social engagement with a brand that is categorized into perceptions based on geographical, demographic, psychographic and sociocultural segmentation.Keywords: Olfactory, Sensory Branding, Non Verbal Comunication, Brand Identity, Product Engagement